Pengelolaan Sumber Belajar oleh Guru Pendidikan Agama Islam - Tiya Sulistiyani (Al-Liqo: Jurnal Pendidikan Islam, 2022)
The importance of learning resources in learning activities cannot be denied anymore. However, learning resources in madrasas and schools generally have not been managed and utilized optimally. The purpose of this study was to determine the management of learning resources by Islamic religious education teachers who focused on textbooks as learning resources at SMP Negeri 1 Tembilahan Hulu. The results of the research through a questionnaire obtained a percentage of 83.33% categorized as "Very Good". Management of learning resources by using textbooks in PAI learning, namely the teacher pays attention to the curriculum and refers to the predetermined curriculum, the teacher analyzes competency standards and basic competencies by adjusting to the needs and level of understanding of students, the teacher arranges the grammar of teaching materials to make it more interesting to collaborate between textbooks and other supporting books, the teacher in compiling the subject matter by using textbooks but does not use only one book source but also uses relevant supporting books, the teacher determines the title of the book according to competency standards, the teacher provides illustrations, pictures, tables and diagrams to make it easier for students to understand.